Pressure injury prevalence and characteristics in patients with COVID-19 admitted to acute inpatient rehabilitation unit - Lu, Weiying; Bloom, Ona; Rathgeber, Melissa; Maltser, Susan (Frontiers in Rehabilitation Sciences, 2023)
Objective: To investigate the incidence and severity of pressure injuries among COVID-19 patients who required acute hospitalization and subsequent acute inpatient rehabilitation (AIR). Design: Data was collected retrospectively from medical charts of COVID-19 patients who were admitted to AIR during April 2020-April 2021. Setting: Acute Inpatient Rehabilitation at a single hospital in the greater New York metropolitan area. Participants: Subjects included COVID-19 patients (N=120) who required acute hospitalization and subsequent acute inpatient rehabilitation, of whom 39 (32.5%) had pressure injuries. Interventions: Not applicable. Main Outcome Measure(s): The incidence, location, and severity of pressure injuries in COVID-19 patients, as well as demographic and clinical characteristics of the acute hospitalization. Results: Among patients who developed pressure injuries, more patients received mechanical ventilation (59% vs. 33%, P<0.05) and tracheostomy (67% vs. 17%, P<0.00001). The lengths of stay were longer in both the intensive care unit (ICU) (34 vs. 15 days, P<0.005), and in acute inpatient rehabilitation (22 days vs. 17 days P<0.05). Conclusions: Pressure injuries were more common in COVID-19 patients who had longer lengths of stay, received mechanical ventilation or tracheostomy, during acute hospitalization. This supports the use of protocols to prioritize pressure offloading in this patient population.